2015
DOI: 10.1021/es506211p
|View full text |Cite
|
Sign up to set email alerts
|

Dioxins and Nonortho PCBs in Breast Milk of Vietnamese Mothers Living in the Largest Hot Spot of Dioxin Contamination

Abstract: Bien Hoa Air Base is the largest dioxin contamination hot spot in Vietnam. In 2012, we recruited 216 mothers who were living in 10 communities around Bien Hoa Air Base and had delivered newborns at a prefecture hospital, and we investigated recent exposure levels of dioxins and nonortho PCBs in their breast milk. 2,3,7,8-Tetrachlorodibenzo-p-dioxin (2,3,7,8-tetraCDD) was present at 2.6 pg/g lipid in primiparae and 2.2 pg/g lipid in multiparae. Among multiparae and total subjects, significant high prevalence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…Particularly, former United States airbases located in Bien Hoa, Da Nang, and Phu Cat are hot spots of dioxin contamination owing to the huge amount of herbicide stored and spilled there during mixing and loading [ 1 , 2 ]. We recently reported that levels of TCDD and PCDDs/Fs in breast milk of mothers residing near hot spots were significantly higher compared with mothers living in unsprayed areas [ 3 , 4 ], suggesting perinatal dioxin exposure including high prenatal dioxin exposure by placental transfer from mothers and postnatal dioxin exposure through breastfeeding to their offspring. Since the brain is undergoing a variety of developmental processes during the perinatal period and is sensitive to neuro-toxins such as dioxins, prenatal exposure by maternal transfer may contribute to adverse neurodevelopmental effects in offspring which appear in later life [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, former United States airbases located in Bien Hoa, Da Nang, and Phu Cat are hot spots of dioxin contamination owing to the huge amount of herbicide stored and spilled there during mixing and loading [ 1 , 2 ]. We recently reported that levels of TCDD and PCDDs/Fs in breast milk of mothers residing near hot spots were significantly higher compared with mothers living in unsprayed areas [ 3 , 4 ], suggesting perinatal dioxin exposure including high prenatal dioxin exposure by placental transfer from mothers and postnatal dioxin exposure through breastfeeding to their offspring. Since the brain is undergoing a variety of developmental processes during the perinatal period and is sensitive to neuro-toxins such as dioxins, prenatal exposure by maternal transfer may contribute to adverse neurodevelopmental effects in offspring which appear in later life [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dioxins are another class of POPs and are a component of certain pesticides, such as Agent Orange, to which ALS has been positively associated [17]. Moreover, elevated levels of the dioxin, 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), has been detected in breast milk from mothers living near the Vietnam Bien Hoa Air Base [122]. Exposure to TCDD from Agent Orange is believed to be an immunotoxin and the probable cause of several types of cancer in Vietnam veterans based on its clear carcinogenicity in experimental animal models [123].…”
Section: Persistent Organic Pollutants (Pops): Pcbs and Dioxinsmentioning
confidence: 99%
“…Deliberate soil ingestion, pica, has been documented during pregnancy in some poverty-stricken populations (>31% in low-income Mexican women and 65% in low-income black women) (Cooksey, 1995;Simpson et al, 2000) further increasing the risk of exposure to dioxins and DLCs through contaminated soils. General daily ingestion of contaminated soils/dusts can also expose infants as demonstrated by elevated levels of PCDD/Fs in breast milk and the umbilical cord in women residing near a highly contaminated site in Vietnam (Nghi et al, 2015;Boda et al, 2018). Wildlife animals such as zebra can ingest soils up to 3 g/kg body mass/day (Turner et al, 2013) while the Colorado mule deer has an estimated soil ingestion of approximately 30 g/d (Arthur and Alldredge, 1979).…”
Section: Introductionmentioning
confidence: 99%